Handling crew sign on/off kapal asing tugboat sinaran oleh PT penascop maritime indonesia cabang palembang - Eki Hairul Saputra; Yudhy Afrianto; Satria (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2026)
Handling the boarding and dismounting of foreign ship crew is a change between the crew on board the ship due to completing the contract or other reasons with the crew who will board the ship based on the plan and schedule previously made by the owner. The implementation of crew changes by PT Penascop Maritim Indonesia Palembang branch encountered several obstacles that caused delays in boarding and dismounting foreign ship crew.The research method used was a qualitative method with informant selection techniques and data obtained through interviews, observation, and documentation in the field. Researchers discovered during their internship at PT Penascop Maritim Indonesia, Palembang branch, that frequent obstacles occurred during the process of boarding and disembarking foreign crew members. These obstacles included the arrival of foreign crew members in Indonesian territory, which resulted in fines/sanctions for the owner. Miscommunication between the agent and the owner also led to delays in crew changes during the boarding and disembarking process. Efforts taken by PT Penascop Maritim Indonesia, Palembang branch, included double-checking emails to avoid miscommunication and overstaying foreign crew in Indonesia, exchanging information about any obstacles encountered in the field, and evaluating the issues